Preliminary study on use of engine oil as wood preservative (2000)
Test samples of Ceiba pentandra Linn, Antiaris africana Engl and Triplochiton Scleroxylon K. schum were treated with spent and new engine oil (SAE40). Three methods of preservative application used are brushing and soaking for 24 hours and 48 hours. The absorption per unit volume of the wood were evaluated. The static bending strength and stiffness values of samples soaked in used engine oil for 48 hours were also obtained. The highest mean absorption rate per unit volume recorded in the study were 30.20kg/m3 for Triplochiton scleroxylon,_and 39.20 kg/m3 for both Ceiba pentandra and Anliaris africana when soaked in new engine oil for 48 hours. The least mean absorption rate of 15.80 kg/m3 19.80kg/m3 and 20.00kg/m3 were recorded for Triplochilon scleroxylon, Antiaris africana and Ceiba pentandra respectively. Following used engine oil application by the brushing method. Statistical analysis carried out showed that both the species and methods of preservative application are significant factors to consider in determining the absorption rate per unit volume of the wood samples. Test results further showed that the engine oil used as the preservative oil had no significant effect on the bending strength of the treated wood samples.